The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1021/acs.cgd.7b00582
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry of Racemic and Enantiopure Organic Crystals for Predicting Enantiomer Separation

Abstract: The separation of an enantiomer from a racemic mixture is of primary relevance to the pharmaceutical industry. The thermochemical properties of organic enantiopure and racemate crystals can be exploited to design an enantioselective crystallization process. The thermodynamic difference between the two crystal forms is accessible by two cycles which give the eutectic composition in solution. The "sublimation cycle" requires calculating the lattice energy and phonon frequencies of the crystal structures. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 78 publications
0
56
0
Order By: Relevance
“…can be derived from the lattice phonon modes as differences in molecular vibrations of isolated and crystallized compound would cancel out. In very flexible systems, this assumptions may not hold . Experimental vibrational lattice frequencies were used to calculate ΔEZPE ΔEZPE=h/2νi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…can be derived from the lattice phonon modes as differences in molecular vibrations of isolated and crystallized compound would cancel out. In very flexible systems, this assumptions may not hold . Experimental vibrational lattice frequencies were used to calculate ΔEZPE ΔEZPE=h/2νi.…”
Section: Resultsmentioning
confidence: 99%
“…Lattice energy calculations have also been shown to be able to resolve energy differences between crystals of the crystallized pure enantiomer and the racemate . These lattice energy differences can be calculated accurately enough to be able to predict relative solubilities and thus the eutectic composition of a compound‐forming system in solution . However, it was recently shown that solely focusing on energy differences of the static lattice is not sufficient for modeling the thermochemistry of molecular crystals at ambient temperature and in solution but thermal corrections and solubilization need to be considered …”
Section: Introductionmentioning
confidence: 99%
“…2 shows that if the lattice energy difference is large, you can condently predict which crystal will form by CSP_0, but if it is small, the outcome is horribly dependent on the energy difference and hence the cancellation of errors in all the other energy terms. Our recent comparison of measured heat capacities at low and ambient temperatures for three pairs of enantiopure and racemic crystals of diverse organic molecules, and other measured thermodynamic quantities, 25 shows that the approximations listed above are not good enough for any of these molecules. The contributions differ in their sensitivity to the molecular and structural differences, particularly the extent to which the molecular vibrational frequencies are unchanged on crystallisation.…”
Section: Csp_thd; Defining the Crystal Energy Landscapementioning
confidence: 99%
“…Differences in the hydrogen bonding motif and consequent frequency shis in the IR spectra between the two crystals, can lead to a temperature dependence of the heat capacity difference around ambient. The performance of our attempts to predict thermal corrections using the harmonic approximation, 25 using rigid molecule J mol or J crys methods similar to those used for larger systems (DOI: 10.1039/c8fd00010g), shows the challenge of predicting free energies or relative solubility at a useful accuracy.…”
Section: Csp_thd; Defining the Crystal Energy Landscapementioning
confidence: 99%
See 1 more Smart Citation